Factors affecting the attack rate of Bemisia tabaci on cucumber - Leite, Germano Leão Demolin; Picanço, Marcelo; Guedes, Raul Narciso Carvalho; Ecole, Carvalho Carlos (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to determine the effects of rainfall, temperature, predators, parasitoids, plant age, leaf chemical composition, levels of leaf nitrogen and potassium, besides density of leaf trichomes, on attack intensity of Bemisia tabaci biotype B on the Cucumis sativus. An increase in the number of whitefly adults and nymphs per leaf was observed with plant aging. A higher number of whitefly adults per leaf and eggs cm-2 was verified in the apical part than in the middle and bottom part of the plants canopy. However, the higher number of whitefly nymphs was observed in the mid-part than in the apical and bottom part of the plant canopy. The incidence of whitefly nymphs was negatively affected with foliar nitrogen. Pentacosane and octacosane positively affected whitefly adults and the first compound also affected the nymphs of this pest species.